Euroaspire III: lifestyle, risk factor and therapeutic management in people at high risk of developing cardiovascular disease from 12 European regions. (22nd September 2015) - Kotseva, K; Jennings, C; De Backer, G; De Bacquer, D; Amouyel, P; Gaita, D; Keil, U; Pajak, A; Reiner, Z; Wood, D
Abstract : Objectives: The third EUROASPIRE survey included people at high cardiovascular risk in general practice. The aim was to determine whether the 2003 Joint European Societies' guidelines on cardiovascular disease prevention in high-risk individuals have been followed in clinical practice. Methods: The EUROASPIRE III survey was undertaken in selected geographical areas and general practices in 12 European countries: Belgium, Bulgaria, Croatia, Finland, Germany, Italy, Latvia, Poland, Romania, Slovenia, Spain and the UK. Consecutive patients, men and women less than 80 years of age, without a history of coronary or other atherosclerotic disease, either started on antihypertensive and/or lipid-lowering and/or anti-diabetes treatments, were identified retrospectively. Data collection was based on a review of the patient's medical notes and a prospective interview and examination at least 6 months after the start of medication. Results: 4366 high-risk individuals (57.7% women) were interviewed (participation rate 76.7%). Overall, 16.9% smoked cigarettes, 43.5% were obese (body mass index ⩾30 kg/m 2 ) and 61.6% were centrally obese (waist circumference ⩾102 cm in men or ⩾88 cm in women), 70.8% had blood pressure ⩾140/90 mm Hg (⩾130/80 in people with diabetes mellitus), 78.9% had total cholesterol ⩾4.5 mmol/l and 30.2% reported a history of diabetes. The risk factor control was very poor, with only 26.3% of patients using antihypertensive medication achieving the blood pressure goal, 30.6% of patients on lipid-lowering medication achieving the total cholesterol goal and 52.9% of patients with self-reported diabetes having haemoglobin A1c less than 6.5%. The use of cardioprotective medication was: aspirin or other antiplatelets 22.0%; beta-blockers 31.2%; ACE inhibitors/angiotensin II receptor blockers 55.7%; calcium antagonists 24.0% and statins 39.9%. Conclusions: The EUROASPIRE III survey shows that the lifestyle of high-risk patients is a major cause for concern, with persistent smoking and high prevalences of both obesity and central obesity. Blood pressure, lipid and glucose control are completely inadequate, with most patients not achieving the targets defined in the prevention guidelines. Primary prevention needs a systematic, comprehensive, multidisciplinary approach, which addresses lifestyle and risk factor management by general practitioners, nurses and other allied health professionals and a health insurance system which invests in prevention.